Abundance Causes Greed in Appropriation from Common Resources. (March 2022) - Nelissen, Rob
Three experiments investigated the possibility that greed is not just a consequence of scarcity but may also result from abundance of common resources. It was predicted that abundance causes greed not through increasing competition but because it reduces social concerns for the outcomes of others, resulting in resource waste. Consistent with these predictions, we found that people take and waste more from common resources if these resources are more—rather than less—abundant. These findings were robust to different types of resources (chocolates and money). Implications of these findings for attempts at sustainable resource use are discussed.